Territorialidades do uso da água ao longo do Canal do Sertão em Alagoas - Silva, Wanubya Maria Menezes da (2016)
Canal do Sertão is the largest and most modern water building of Alagoas. It is na important geographic object introduced in semiarid area in order to mitigate the problems arising due drought periods that devastate semiarid region from Alagoas. In this sense, this research aimed to understand how territorialities are formed on use of Canal do Sertão water in Delmiro Gouveia and Água Branca, AL, on small and medium-sized family farms and local land properties. It was conducted through theoretical approach of the concepts of territory, territorialization and territoriality. On this perspective we made a synthesis of territoriality idealized by Alagoas government to future irrigated areas and designed a development prognosis to the towns locus of this research. This paper presents a study of the concepts underlying the analysis combined with work and field research. In this sense, in order to achieve the proposed objective, we collected official data on government offices directly involved on Canal do Sertão implemantation, and federal agencies, such as IBGE and Ministry of Social Development. Moreover, we performed non-directive interviews with subjects that use water from Canal do Sertão. We could, therefore, infer about the use of water and the dynamics of territoriality surrounding the Canal do Sertão.